Death Due to Blunt Force Trauma Disguised as Suicide by Hanging: A Case Report - Puspitasari, Meylia; Bumi Agung, I Gusti Lanang; Yudianto, Ahmad; Purwaningsih, Eni; Widodo, Wimbuh Tri (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Simulated hanging, also referred to as pseudohanging or postmortem suspension, is a form of death-scene manipulation in which a body is positioned to resemble suicidal hanging. Distinguishing true hanging from simulated hanging remains a medicolegal challenge because no single autopsy finding is pathognomonic. Case Presentation: A 31-year-old woman was reported to have been found in a hanging-like position on the stairs of her house. Initial scene information suggested suicide by hanging. External examination revealed fixed purple-red livor mortis, complete rigor mortis, abrasions and contusions on the face and scalp, and no characteristic ligature mark on the neck. Internal examination showed right scalp hemorrhage, subdural and bilateral subarachnoid hemorrhage, blood extravasation in the neck soft tissues, and an intact hyoid bone. The available record did not document the measured volume of the intracranial hemorrhage, a detailed map of subarachnoid extension, the presence or absence of cerebral edema, toxicological findings, histopathological confirmation, or interpretable touch-DNA results. Conclusion: The integration of scene information, external examination, internal autopsy findings, and the limitations of the available supportive evidence indicated that simulated hanging was more probable than true suicidal hanging. The most plausible cause of death was blunt force trauma to the head with intracranial hemorrhage; however, the independent lethality of the intracranial hemorrhage could not be quantified because detailed volumetric and cerebral edema data were unavailable. This case emphasizes the need for complete medicolegal autopsy and careful correlation between scene findings and biological evidence when death is initially suspected to be suicidal hanging.